The role of employees for post-entry firm growth - Andreas Koch; Jochen Späth; Harald Strotmann (Institut für Angewandte Wirtschaftsforschung (IAW), 2012)
While the majority of existing studies on the determinants of post-entry firm growth focus on the role of the founders or on the impact of firm-specific characteristics like size, age or industry affiliation, a possible impact of the characteristics of a start-up's workforce on post-entry growth has been widely neglected in the literature so far. Based upon a comprehensive panel dataset of establishments in Germany, this paper contributes to fill this gap and examines the role of the initial employment structure with respect to qualification, age, gender and nationality for post-entry employment growth measured both in terms of employees and in terms of fulltime equivalents. Moreover, it is analyzed whether the use of flexible work forms like regular part-time and / or marginal employment in the year of foundation affects post-entry growth. Our empirical results confirm that in particular the initial qualification structure of a start-up's employees matters for post-entry growth. Establishments using flexible work forms show higher post-entry growth with respect to total hours worked, but a significantly lower growth with respect to the number of employees.
Keywords: J24; L10; L25; 330; Start-ups; post-entry performance; firm growth; job quality; flexibility; human capital; Unternehmensgründung; Unternehmenswachstum; Arbeitskräfte; Qualifikation; Arbeitszeitgestaltung; Schätzung; Deutschland